Quality changes in virgin coconut oil produced by centrifuge process during storage - Mauricio, Rosela A. (UP College of Home Economics, 2012)
ABSTRACT The quality change ins during storage of VCO produced by the centrifuge process (ITDI wet method) were investigated. Based on the optimized headspace generation parameters of 80°C incubation temperature for 10 minutes, the volatile compounds were monitored in the headspace of VCO samples stored at 30°, 40°, 50°C at different sampling intervals. The volatile compounds that were tentatively identified by comparison with the NIST mass spectrum library were those more associated with antimicrobial activity and coconut aroma. Very low initial moisture content was detected (0.06%) in the VCO samples produced by the ITDI wet method with minor changes monitored regardless of storage temperature. The initial FFA content of the sample was 0.07%. which slowly increased after storage at temperatures of 30°, 40°, and 50°C. for 244 days to 0.09, 0.13 and 0.17% respectively corresponding to k values (rate constant) of 0.000008, 0.0002, and 0.0004. The scores for the sensory attributes such as latik and nutty aroma and flavor were high while the rancid and acid aroma and flavor are very low. Negative correlations were observed in the FFA formation and latik and nutty aroma and flavor as well as in the moisture content of VCO. Positive correlation was found in the FFA and rancid and acid flavor as well as moisture content and acid flavor. However, negative correlations of the sensory attributes - rancid and acid aroma with FFA and moisture content were also observed. These correlations, however, are very low and not statistically significant (p>0.05). Principal components analysis (PCA) of the descriptive sensory data reduced the eleven sensory attributes to three principal components for the samples stored at 30° and 40°C, and two principal components for samples stored at 50°C. A first order equation model of FFA foramtion was used in the shelf life estimation of the VCO samples. Samples stored at 30°, 40°, and 50°C gave an estimated shelf life of 583,362, and 291 days, respectively.